Enhancing Student Competence Through Internships at SMEC Hospital in Medan: Soft Skills and Ethics Development - Ika Devi Perwitasari; Jodi Hendrawan; Yanti Yusman (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2025)
Internship programmes are an important part of strengthening student competencies, particularly in preparing them for the complex and dynamic world of work. This article discusses the implementation of student internships in the Computer Systems Study Programme at SMEC Eye Hospital in Medan as part of community service aimed at improving students' soft skills, professional ethics, and adaptability in a public service environment. This study employed a qualitative descriptive approach with a case study design, involving four students over three months in the medical records unit, general administrative services, and BPJS services. The results showed significant improvements in work responsibility, interpersonal communication, and awareness of work ethics. Students successfully achieved the target of archiving at least 150 files per day and demonstrated effective communication skills in serving patients and collaborating with hospital staff. Field supervisors noted that the students were quick learners and adept at performing their tasks. The discussion in this article links these findings to relevant literature, reinforcing the importance of cross-sector collaboration between technology education institutions and healthcare services. This article recommends expanding the number of internship participants, using quantitative evaluative instruments, and strengthening the integration of students into the hospital's digital system in the future.